The Role of Artificial Intelligence in Creating New Business Models in The Digital Economy: from Digitalisation to Fully Automated Solutions - S. V. Savin; A. D. Murzin (Мир новой экономики, 2024)
Purpose of the article is to study the impact of artificial intelligence (AI) on the transformation of business models in the digital economy.   Object of the study are companies implementing AI to automate processes and improve efficiency.   Subject of the study is the changes in key elements of business models: the creation, delivery, and monetization of value.   Methodology includes the analysis of practical cases, the calculation of return on investment (ROI), and the assessment of reductions in operating costs.   Scientific novelty lies in the development of an approach to fully automating AI-based business processes, and identifying related challenges, such as problems with trust in AI systems, and ethical aspects of its use.   Practical significance of this work is to demonstrate the need for reviewing existing business models, and investing in AI infrastructure, to increase the competitiveness of companies in the digital economy.